Globaalivirtojen paikallistuminen: Sellutehdas, ihmiset ja paikka Kemijärvellä - Rönkä, Anna; Sarkki, Simo (Alue- ja ympäristötutkimuksen seura, 2011)
Globalization has changed socio-economical settings all over the world and it has also affected Finnish forest industry. Globalization can be witnessed when factories have been closed down in Finland, like in Kemijärvi, and new factories have been opened in new locations mainly in the global south. In this article, we examine the views of former workers of Kemijärvi pulp mill closing via anthropologist Arjun Appadurai’s idea of globalization, which consists of five flows or scapes: technoscape, financescape, ideoscape, mediascape and ethnoscape. Through our content analysis of theme interviews we noticed that the workers’ views could be categorized with Appadurai’s theory. The former workers’ views of the reasons behind the pulp mill closing were different than those in the official statements of the pulp mill management. The workers did not understand why the profit-making factory had to close down. However, some parts of the theory did not fit the Kemijärvi case. We found that, in his theory, Appadurai has neglected the influence of place in shaping the global flows.